2023 KLATSKY ENDOWED LECTURE IN HUMAN RIGHTS: THE FORGOTTEN CRIME: FORGING A CONVENTION FOR CRIMES AGAINST HUMANITY - Sadat, Leila Nadya (Case Western Reserve journal of international law, 2024)
Thank you, Dean Scharf, for your generous introduction. Being honored with the Klatsky Humanitarian Award is humbling given the distinguished individuals who have received it in prior years. It is also special to be here today with you, as we have collaborated on many projects in the past, including during the very early stages of the Crimes Against Humanity Initiative,1 the subject of today's lecture. I would also like to thank Mr. Bruce Klatsky2 for his kind words, service on the Board of Human Rights Watch, and generous support of this award and associated endowed lecture series.